Mechanical characterization of highly heterogeneous brittle materials by optical techniques. (July 2022) - Suarez, Laura; Kajberg, Jörgen; Forsberg, Fredrik; Jonsén, Pär
Highlights: The macro-response of MnFeSi-slag under quasi-static compression conditions is highly dependent on the structure and composition of the material. The strength of MnFeSi-slag samples depends strongly on the inclusion density, distribution and level of attachment to the matrix. The texture of MnFeSi-slag samples characterized by X-ray Computed Tomography together with mechanical tests suggests a strong relation between the phase-to-inclusion ratio and the brittleness of the material. The evolution of the strain field captured by DIC shows a mechanical behavior of a composite-like material where random failure of the components caused high variability of the elastic parameters. Abstract: Fragmentation processes like crushing and grinding are complex and extensively energy-consuming activities in the mining and mineral processing industry. By studying the processes and the typically brittle material involved in a virtual environment, i.e. numerical simulations, knowledge will be gained to support improvement of the efficiency and thereby meet established environmental goals. Although, a challenge is the lack of experimental data both for calibration and validation hampering the development of constitutive models. As a case of study, a mechanical characterization of MnSiFe-slag was performed. X-ray Computed Tomography was used for 3D imaging and quantitative characterization of the material texture, with focus on the shape, size and spatial distribution of inclusions. Diametral and axial compressive tests under quasi-static conditions were used to load the mineral material and obtain a strain field ( ε ) during increasing and cyclic loading until failure accounting for progressive damage. The evolution of the strain captured by digital image correlation (DIC) techniques exposed a mechanical behavior of composite-like material where random failure of the components caused high variability of the elastic parameters. These were found to be load dependent and they are strongly related to the ability of the material to internal re-arrangement during loading. Irreversible damage affects the structure of the material and it is perceived as non-linearities in the load–strain curves. It was found a degradation of the material under repetitive loading. A decrease of the elastic modulus exposes a weakening of the matrix and dominant behavior of the inclusions on the mechanical response of the material.